Splitting type viscosity methods for inclusion and fixed point problems on Hadamard manifolds - Dilshad, Mohammad; Khan, Aysha; Akram, Mohammad (AIMS mathematics, 2021)
In this article, we suggest and analyze the splitting type viscosity methods for inclusion and fixed point problem of a nonexpansive mapping in the setting of Hadamard manifolds. We derive the convergence of sequences generated by the proposed iterative methods under some suitable assumptions. Several special cases of the proposed iterative methods are also discussed. Finally, some applications to solve the variational inequality, optimization and fixed point problems are given on Hadamard manifolds.